Implementasi Bioretensi Untuk Pengairan Tanaman Hidroponik Di Griya Katulampa - Widiyanti, Astrini; Arifin, Hadi Susilo; Arifjaya, Nana Mulyana (Pusat Penelitian Lingkungan Hidup, IPB (PPLH-IPB) dan Program Studi Pengelolaan Sumberdaya Alam dan Lingkungan, IPB (PS. PSL, SPs. IPB), 2019)
Bogor City has been declared a City of Water Sensitivity. For this reason, each housing needs to process domestic wastewater, one of which uses bioretension, before entering the nearest surface water body. The purpose of this study was to determine the quality of domestic wastewater from Griya Katulampa housing, where the drainage channels flow directly into the Ciliwung River and analyze the effectiveness of the use of bioretension to improve the quality of domestic wastewater caused. Bioretence with filter media includes 50% sandy soil, top soil 20-30%, and mulch 20-30% and the vegetation used consists of Kana (Canna sp), Air Jasmine (Echinoderus palifolius), Cyperus (Cyperus papyrus) made. Measuring the quality of domestic wastewater is carried out at the installation inlet and outlet. The result showed that domestic wastewater from Griya Katulampa was still below the specified quality standard. Bioretence with fiber media and cane plants can be used to reduce TSS as a parameter that has a value above the specified quality standard. To increase added value, water spinach can be planted as a hydroponic plant that can grow and has the highest productivity value.